Dendrogeomorphic reconstruction of lahar activity and triggers: Shiveluch volcano, Kamchatka Peninsula, Russia - Salaorni, E.; Stoffel, Markus; Tutubalina, O.; Chernomorets, S.; Seynova, I.; Sorg, Annina (Bulletin of Volcanology, 2017)
Lahars are highly concentrated, water-saturated volcanic hyperconcentrated flows or debris flows containing pyroclastic material and are a characteristic mass movement process on volcanic slopes. On Kamchatka Peninsula (Russian Federation), lahars are widespread and may affect remote settlements. Historical records of past lahar occurrences are generally sparse and mostly limited to events which damaged infrastructure on the slopes or at the foot of volcanoes. In this study, we present a tree-ring-based reconstruction of spatiotemporal patterns of past lahar activity at Shiveluch volcano. Using increment cores and cross sections from 126 Larix cajanderi trees, we document 34 events covering the period AD 1729–2012. Analyses of the seasonality of damage in trees reveal that 95% of all lahars occurred between October and May and thus point to the predominant role of the sudden melt of the snow cover by volcanic material. These observations suggest that most lahars were likely syn-eruptive and that lahar activity is largely restricted to periods of volcanic activity. By contrast, rainfall events do not seem to play a significant role in lahar triggering.